A Brief Introduction of Biometrics and Fingerprint Payment Technology - Kumar, Dileep; Ryu, Yeonseung (International Journal of Advanced Science and Technology, 2017)
In this paper we have survey on biometric payment system. Biometric payment system is used for various kinds of payment system instead of the tension of cards to put with them and to memorize theirs difficult passwords and pin numbers. Biometric payment system is much safe and secure and very easy to use and even without using any password or secret codes to remember as compare with previous system like credit card payment system, wireless system and mobile system etc. Biometric payment system is reliable, economical and it has more advantages as compare with others. In daily life the usage of credit cards, check card for shopping, bus card, subway card for traveling, student card for library and department, and many kinds of cards for unlimited purposes and so on. So problem is that a person has to take many cards and has to remember their passwords or secret codes and to keep secure to take with him all time. So the biometric payment system will solve this problem. Greater adoption of biometric payment system will drive down the cost of biometric readers and thus making it more affordable to small business owners. We really need alternate payment systems. This "perpetual toll" to credit card companies has to stop.